2005
DOI: 10.1038/ja.2005.99
|View full text |Cite
|
Sign up to set email alerts
|

Lichenicolins A and B, New Bisnaphthopyrones from an Unidentified Lichenicolous Fungus, Strain LL-RB0668

Abstract: Lichenicolous fungus LL-RB0668 was isolated from a processed lichen thallus on a modified Lilly-Barnett solid medium. Two new bisnaphthopyrone compounds, lichenicolins A (1) and B (2), were isolated from the culture broth of this organism fermented on a rice-based solid medium. These results demonstrate that lichenassociated fungi potentially are a good resource for new bioactive natural products for current screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Although ecological, taxonomical, and phylogenetic studies of North American lichens have been active study areas in lichenology (Geiser et al, 2010; (He et al, 2005;Lawrey, 1989;Shrestha & St. Clair, 2013b). This study provides data based on the first broad-scale screening of lichens collected from different parts of the United States against four different pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although ecological, taxonomical, and phylogenetic studies of North American lichens have been active study areas in lichenology (Geiser et al, 2010; (He et al, 2005;Lawrey, 1989;Shrestha & St. Clair, 2013b). This study provides data based on the first broad-scale screening of lichens collected from different parts of the United States against four different pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cyclodipeptide cordysinin A, first identified in the caterpillar fungus C. sinensis [ 32 ], was detected in our metabolomic data. Additional compounds first identified in non-insect pathogens were also detected, including the antibiotic fumimycin first reported in Aspergillus fumisynnematus [ 33 ], lichenicolin A reported in a lichenicolous fungus [ 34 ], alkaloid sinensine B from the basidiomycete Ganoderma sinense [ 35 ], and cycloheximide acid A from a bacterium [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, fungi interacting with lichens were reported to produce natural products such as bis-naphtopyrones and lichenicolins A and B, both of which have activity against Gram-positive bacteria [73]. Co-culturing an unidentified bacterium with the fungus Libertella sp., diterpenoids-including libertellenone A-D--were discovered.…”
Section: Bacterial-fungal Interactions and Natural Product Discoverymentioning
confidence: 98%